Impact of water resevoir filling of an hydroeletric plant on dynamics of an araucaria forest fragment in santa catarina Impacto do enchimento do reservatório de uma uhe sobre a dinâmica de um fragmento de floresta ombrófila mista em santa catarina - Lima C.L.* (2018)
© 2018, Universidade Federal de Santa Maria. All rights reserved.We aimed to investigate the impact of the water reservoir of a hydroelectric power station on the tree component dynamics in an adjacent forest. For this, we allocated 48 plots in three sectors: bottom, adjacent to water reservoir, middle slope and upper slope. One year after the water filling, we measured (circumference at breast height – cbh and identified all trees with cbh) ≥ 15,7 cm, followed by the dynamics study in the next year, with the re-measurement of survival trees and quantification of mortality and recruitment. We evaluated environmental variables (edaphics, topographics and environmental impacts). We determined the dynamics rates and applied a Principal Component Analysis (PCA) to the ordination of environmental variables and analyzed the influence of environmental gradients on community demographics rates through logistic regression. The dynamics presented number of individuals stability, but a greater basal area gain (3.64%.year-1) than loss (1.62%.year-1). There were differences among sectors, with a greater loss in bottom sector (2.51%.year-1) than others. There was a weak relation between analyzed environmental variables, suggesting that trees growth is mostly related to non-measured variables. The present study indicates that, two years after the water filling, it is possible to detect the short-term impacts of the reservoir of hydroelectric power station on tree community.